Assessment and selection of the best treatment alternative for infectious waste by modified Sustainability Assessment of Technologies methodology. Issue 1 (December 2016) - Rafiee, Ata; Yaghmaeian, Kamyar; Hoseini, Mohammad; Parmy, Saeid; Mahvi, Amirhosein; Yunesian, Masud; Khaefi, Mehran; Nabizadeh, Ramin
Abstract Background Improper treatment of infectious waste can cause numerous adverse environmental and health effects such as transmission of diseases through health personnel and other susceptible groups, who come in contact with such wastes. On the other hand, selection of appropriate treatment alternatives in infectious waste management has become a challenging task for public health authorities especially in developing countries. The objective of this paper is to select the best infectious waste treatment alternative by the modified Sustainability Assessment of Technologies (SAT) methodology, developed by the International Environmental Technology Center of the United Nations Environment Program (IETC-UNEP). Methods SAT methodology consists of three main components, including screening, scoping and detailed assessment. In screening, different infectious waste treatment alternatives undergo screening using the finalized environmental and technical criteria. Short-listed treatment options from the previous step, then go through the comprehensive scoping and detailed assessment (2nd and 3rd components) which is more qualitative and quantitative in nature. An empirical case in Tehran, the largest city in Iran, is provided to illustrate the potential of the proposed methodology. Results According to the final score, "Hydroclave", was the most suitable infectious treatment technology. The ranking order of the treatment alternatives were "Autoclave with a shredder", "Autoclave", "Central Incineration" and "chemical treatment" on the basis of technical, economical, social and environmental aspects and their related criteria. Conclusions According to the results it could be concluded that the top ranking technologies basically have higher scores in all the aspects. Hence it is easier to arrive at a decision for the final technology selection based on the principles of sustainability.